(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
The article is an autobiographical account by a theater artist who sees herself as a “theatrical nomad.” She recounts her journey from childhood in Romania, influenced by puppet theater, to her studies in Prague, where she deepened her connection with animated forms of theater. Back in Romania, she performed during the communist regime, using metaphors to bypass censorship. Later, she traveled to the United States and other countries with her performances and, for love, eventually moved to the U.S. and then to Geneva. Throughout the text, she reflects on her artistic vocation, the social impact of theater, and her choice to live as an itinerant artist dedicated to creating meaningful performances for both children and adults.